Remote sensing driven lithological discrimination within nappes of the Naukluft Nappe Complex, Namibia - Van der Merwe, Hendrik Naude (Stellenbosch : Stellenbosch University, 2015)
Thesis (MSc)--Stellenbosch University, 2015.